INTEGRATION OF LOCAL WISDOM IN INDONESIAN LANGUAGE LEARNING AT UPT SDN 21 BANGKALA, JENEPONTO REGENCY - Marniati Marniati; M. Agus M. Agus; Aliem Bahri (Jurnal Konseling Pendidikan Islam, 2026)
This research aims to describe: (1) the integration of local wisdom in Indonesian learning planning at UPT SDN 21 Bangkala, Jeneponto Regency, (2) the implementation of local wisdom in the implementation of Indonesian language learning, and (3) the supporting and inhibiting factors in the integration of local wisdom in the learning. This study uses a qualitative approach with a descriptive type of research. The research subjects include classroom teachers and students, while data collection techniques are carried out through observation, interviews, and documentation. Data is analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that: (1) at the planning stage, teachers have integrated elements of local wisdom through the selection of materials, learning objectives, and the preparation of activities relevant to regional culture, although it is still not completely systematic. (2) In the implementation stage, teachers apply local wisdom through the use of text examples, local folklore, contextual learning media, and discussions that raise students' cultural experiences. Students also show enthusiasm and active involvement when material is associated with the local culture. (3) Supporting factors for the integration of local wisdom include the availability of cultural resources in the surrounding environment, school support, and the proximity of students to the cultural context. The inhibiting factors include the limitation of teaching materials that contain local wisdom, the lack of teacher training, and the lack of optimal use of culture-based learning media. This study concludes that the integration of local wisdom in Indonesian learning at UPT SDN 21 Bangkala has been implemented, but it still needs to be strengthened in the aspects of planning and providing teaching materials so that the implementation of learning based on local wisdom can take place more optimally.